Pengaruh Tingkat Kesulitan Keuangan Perusahaan TerhadapKonservatisme Akuntansi - EKO WIDODO LO (The Indonesian Journal of Accounting Research, 2013)
This research tests the influence of a company’s financial distress on its accounting conservatism. The issue of this research is the prediction difference between positive accounting theory and signaling theory about the influence of a company’s financial distress on its accounting conservatism. Sample in this study consists of manufacturing companies that were listed at Jakarta Stock Exchange since 1994 to 2002. Sample consists of 108 companies or 864 observations. This study develops a testing and developing procedure of accounting conservatism instrumental variables by using more accounting conservatism attributes. Hypotheses are examined by using Ordinary Least Squares Regression and Generalized Method of Moments Regression.The results of empirical tests indicate that a company’s financial condition positively influences its accounting conservatism. These support signaling theory prediction.